Feasibility Study of Regional Planning of Palm Oil Revenue Sharing Fund in Improving the Welfare of the People of Sei Dadap District - Ardi Nugroho; Abdi Sugiarto (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to examine the Feasibility Study of Regional Planning of the Palm Oil Revenue Sharing Fund in Improving the Welfare of the People of Sei Dadap District. The qualitative research method provides an in-depth and comprehensive approach in the feasibility study of the planning of the Palm Oil Revenue Sharing Fund. By combining interviews, observations, and group discussions, this study can explore a better understanding of the needs and expectations of the people of Sei Dadap District. Systematic data analysis and the use of triangulation also ensure the validity and reliability of the findings, which in turn can support better decision-making in regional planning and utilization of Palm Oil DBH. This study emphasizes the importance of sustainability in programs funded by palm oil DBH. Sustainable programs that pay attention to environmental aspects, such as waste management and reforestation, as well as skills training for communities, ensure that the positive impact of DBH will continue to be felt by future generations. The overall results of this study indicate that with effective regional planning, community participation, and strict supervision, the optimization of the Palm Oil Revenue Sharing Fund is able to bring a significant improvement in welfare to the people of Sei Dadap District. DBH not only improves the quality of life of the community but also promotes social stability, local economic growth, and environmental sustainability. With the implementation of these strategies, Sei Dadap District is expected to be able to realize sustainable and equitable community welfare.